Positive psychology interventions in in-patients with depression: influences of comorbidity and subjective evaluation of the training programme - Antje Stemmler; Regina Staehle; Tina Heinemann; Matthias Bender; Juergen Hennig (BJPsych Open, 2021)
Background Studies on positive psychology interventions (PPIs) have frequently demonstrated benefits for healthy participants and patients. However, effect sizes are moderate, and underlying inter-individual differences in responses were rarely investigated.